Modernistična estetika emocij in lirski diskurz - Juvan, Marko (Slavistična revija, 2010)
The aesthetization and abstraction of emotion in the Slovenian lyrical poetry of the 1970s and 1980s ia considered in the framework of recent transnational, paratactic, and polycentric understandings of modernism. It is also interpreted as a poetic reaction to the particular political Slovenian context of the "leaden 1970s".
Keywords: 1970/1985; aesthetics; communism; čustva; estetika; komunizem; lirika; modernizem; Slovene literature; slovenska književnost; slovenska poezija